Transition impact on foreign trade growth in the Czech Republic - Esmaeel, Ezat Sabir (Univerzita Pardubice, 2010)
Economic transition in the Czech Republic started in the early 1990s and privatized most of the firms, the ownership of privatized firms reduce the unit of labor cost and increases productivity and then the amount of profit. The Czech Republic government liberalized almost all the prices, privatized most of the economy, decentralized the wage setting, and opened the country to the foreign trade with nearly balanced budget. In general, the transition impact on economic performance in the Czech Republic was positive. In the empirical work, the regression analysis of Czech foreign trade during 1993 to 2008 shows that the exports and imports depending on GD; FD; LW; UR; ER; EC; LR and IR Simultaneously. This model of Czech foreign trade was able to explain 96.3 percent of the variation in Czech exports and 97.5 percent of imports, which is a strong result. In addition, the two significant variables, which have a big relationship with exports and imports, are labor wages and gross domestic product. In addition, the first and the more important sector for the Czech foreign trade share during 1999 to 2008 is Machinery and transport equipment. The first and the more important commodity contributed in Czech foreign trade during the period of study is (Nuclear reactors, boilers, machinery and mechanical appliances).
Keywords: ekonomická transformace; zahraniční obchod; privatizace; sektorová struktura; vícenásobná regrese; economic transition; foreign trade; privatization; sector share; multiple regression model